HYDRAULIC TEST SPRINKLER-EQUIPPED SIGNAL DELUGE VALVES - A. А. Herasimovich; K. D. Yashin (Doklady Belorusskogo gosudarstvennogo universiteta informatiki i radioèlektroniki)
The complex bench hydraulic tests signal sprinkler, deluge valve are conducted. The technique of carrying out of tests is described. Checked tightness and durability of the valve body at a pressure of 2,4 MPa inside the valve. A decision on its performance and compliance with the standards of fire safety is issued.